The Impact of Online Reviews and Social Media on Brand Loyalty: Evidence from MS Glow Skincare Consumers in Batam City - Sitoris Wehalo; Mauli Siagian (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the influence of online reviews and the role of social media on brand loyalty toward MS Glow skincare products in Batam City. The population of this research consists of consumers in Batam City who have purchased and used MS Glow skincare products and have been exposed to online reviews and social media content related to the brand. A total of 204 respondents were selected using the Jacob Cohen sampling approach. Data were analyzed using multiple linear regression techniques. The analysis process included data quality testing, classical assumption tests, effect analysis, and hypothesis testing. The results of the multiple linear regression analysis indicate that online reviews contribute 33.7% to brand loyalty, while the role of social media contributes 66.9%. Furthermore, the coefficient of determination (R²) reveals that online reviews and social media collectively explain approximately 58.1% of the variance in brand loyalty. The findings from the t-test and F-test demonstrate that both online reviews and social media have a positive and statistically significant effect on brand loyalty, both individually and simultaneously, toward MS Glow skincare products in Batam City.